Antibacterial activity of extracts and fractions of wood ear mushroom (Auricularia auricula) - Ika Kurnia Sukmawati; Elis Susilawati; Sindi Dwi Putri (Universitas Ahmad Dahlan, 2019)
Infection is a disease caused by pathogenic bacteria, such as Staphylococcus aureus, Escherichia coli, Bacillus cereus, and Pseudomonas aeruginosa. The wood ear mushroom (Auricularia auricula) has been empirically and scientifically proven as an agent that can treat infections because it contains antimicrobial properties like polysaccharide and protein complex. This study aimed to determine the antimicrobial activity of the A. auricula extracts and fractions. The first stage of the test comprised the collection, determination, and processing of the test plant. The simplicia was characterized by its water content, ash content, acid solubility, and total ash content. The next step was reflux extraction using 96% ethanol. After a concentrated extract was formed, it was subjected to phytochemical screening and fractionation using liquid-liquid extraction (LLE) with n-hexane, ethyl acetate, and methanol-water solvents. Each of the A. auricula extracts and fractions was tested for antimicrobial activity. Microdilution method was employed to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC), which were later compared with the antibiotic properties of tetracycline. Scanning Electron Microscopy (SEM) was used to observe any morphological changes in the tested bacteria. The MICs of the A. auricula extract, n-hexane fraction, and ethyl acetate fraction against S. aureus were 256 μg/mL, 128 μg/mL, and 64 μg/mL, respectively. However, the bactericidal effects of the test mushroom were not achieved in the experiment. Based on the MICs, the ethyl acetate fraction has the best inhibitory activity. Moreover, the bioautography test of this fraction produced Rf value= 0.78, implying the formation of a zone of growth inhibition. The SEM of the A. auricula extracts and fractions proved that this mushroom altered the morphology of S. aureus bacteria—i.e., the cells became rounded and tapered and showed indications of cell shrinkage and damage. As a conclusion, the ethyl acetate fraction of A. auricula has the best antimicrobial activity against S. aureus.